Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the tangent and normal lines to the graph of [tex]\(x^2 - \sqrt{3}xy + 4y^2 = 235\)[/tex] at the point [tex]\((\sqrt{3}, 8)\)[/tex], follow these steps:
1. Find Partial Derivatives:
Compute the partial derivatives of the given equation with respect to [tex]\(x\)[/tex] and [tex]\(y\)[/tex].
[tex]\[ F(x, y) = x^2 - \sqrt{3}xy + 4y^2 - 235 \][/tex]
The partial derivative with respect to [tex]\(x\)[/tex] is:
[tex]\[ F_x = \frac{\partial F}{\partial x} = 2x - \sqrt{3}y \][/tex]
The partial derivative with respect to [tex]\(y\)[/tex] is:
[tex]\[ F_y = \frac{\partial F}{\partial y} = -\sqrt{3}x + 8y \][/tex]
2. Evaluate Partial Derivatives at Given Point:
Evaluate [tex]\(F_x\)[/tex] and [tex]\(F_y\)[/tex] at the point [tex]\((\sqrt{3}, 8)\)[/tex].
[tex]\[ F_x(\sqrt{3}, 8) = 2(\sqrt{3}) - \sqrt{3}(8) = 2\sqrt{3} - 8\sqrt{3} = -6\sqrt{3} \][/tex]
[tex]\[ F_y(\sqrt{3}, 8) = -\sqrt{3}(\sqrt{3}) + 8(8) = -3 + 64 = 61 \][/tex]
3. Find the Slope of the Tangent Line:
The slope of the tangent line to the curve at [tex]\((\sqrt{3}, 8)\)[/tex] is given by:
[tex]\[ \text{slope of tangent line} = -\frac{F_x}{F_y} = -\frac{-6\sqrt{3}}{61} = \frac{6\sqrt{3}}{61} \][/tex]
4. Find the Equation of the Tangent Line:
The equation of the tangent line at [tex]\((\sqrt{3}, 8)\)[/tex] is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Substituting [tex]\(m = \frac{6\sqrt{3}}{61}\)[/tex], [tex]\(x_1 = \sqrt{3}\)[/tex], and [tex]\(y_1 = 8\)[/tex]:
[tex]\[ y - 8 = \frac{6\sqrt{3}}{61}(x - \sqrt{3}) \][/tex]
5. Find the Slope of the Normal Line:
The slope of the normal line is the negative reciprocal of the slope of the tangent line:
[tex]\[ \text{slope of normal line} = -\frac{1}{\text{slope of tangent line}} = -\frac{1}{\frac{6\sqrt{3}}{61}} = -\frac{61}{6\sqrt{3}} = -\frac{61\sqrt{3}}{18} \][/tex]
6. Find the Equation of the Normal Line:
The equation of the normal line at [tex]\((\sqrt{3}, 8)\)[/tex] is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Substituting [tex]\(m = -\frac{61\sqrt{3}}{18}\)[/tex], [tex]\(x_1 = \sqrt{3}\)[/tex], and [tex]\(y_1 = 8\)[/tex]:
[tex]\[ y - 8 = -\frac{61\sqrt{3}}{18}(x - \sqrt{3}) \][/tex]
Thus, the equations are:
- The tangent line is [tex]\[ y - 8 = \frac{6\sqrt{3}}{61}(x - \sqrt{3}) \][/tex]
- The normal line is [tex]\[ y - 8 = -\frac{61\sqrt{3}}{18}(x - \sqrt{3}) \][/tex]
1. Find Partial Derivatives:
Compute the partial derivatives of the given equation with respect to [tex]\(x\)[/tex] and [tex]\(y\)[/tex].
[tex]\[ F(x, y) = x^2 - \sqrt{3}xy + 4y^2 - 235 \][/tex]
The partial derivative with respect to [tex]\(x\)[/tex] is:
[tex]\[ F_x = \frac{\partial F}{\partial x} = 2x - \sqrt{3}y \][/tex]
The partial derivative with respect to [tex]\(y\)[/tex] is:
[tex]\[ F_y = \frac{\partial F}{\partial y} = -\sqrt{3}x + 8y \][/tex]
2. Evaluate Partial Derivatives at Given Point:
Evaluate [tex]\(F_x\)[/tex] and [tex]\(F_y\)[/tex] at the point [tex]\((\sqrt{3}, 8)\)[/tex].
[tex]\[ F_x(\sqrt{3}, 8) = 2(\sqrt{3}) - \sqrt{3}(8) = 2\sqrt{3} - 8\sqrt{3} = -6\sqrt{3} \][/tex]
[tex]\[ F_y(\sqrt{3}, 8) = -\sqrt{3}(\sqrt{3}) + 8(8) = -3 + 64 = 61 \][/tex]
3. Find the Slope of the Tangent Line:
The slope of the tangent line to the curve at [tex]\((\sqrt{3}, 8)\)[/tex] is given by:
[tex]\[ \text{slope of tangent line} = -\frac{F_x}{F_y} = -\frac{-6\sqrt{3}}{61} = \frac{6\sqrt{3}}{61} \][/tex]
4. Find the Equation of the Tangent Line:
The equation of the tangent line at [tex]\((\sqrt{3}, 8)\)[/tex] is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Substituting [tex]\(m = \frac{6\sqrt{3}}{61}\)[/tex], [tex]\(x_1 = \sqrt{3}\)[/tex], and [tex]\(y_1 = 8\)[/tex]:
[tex]\[ y - 8 = \frac{6\sqrt{3}}{61}(x - \sqrt{3}) \][/tex]
5. Find the Slope of the Normal Line:
The slope of the normal line is the negative reciprocal of the slope of the tangent line:
[tex]\[ \text{slope of normal line} = -\frac{1}{\text{slope of tangent line}} = -\frac{1}{\frac{6\sqrt{3}}{61}} = -\frac{61}{6\sqrt{3}} = -\frac{61\sqrt{3}}{18} \][/tex]
6. Find the Equation of the Normal Line:
The equation of the normal line at [tex]\((\sqrt{3}, 8)\)[/tex] is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Substituting [tex]\(m = -\frac{61\sqrt{3}}{18}\)[/tex], [tex]\(x_1 = \sqrt{3}\)[/tex], and [tex]\(y_1 = 8\)[/tex]:
[tex]\[ y - 8 = -\frac{61\sqrt{3}}{18}(x - \sqrt{3}) \][/tex]
Thus, the equations are:
- The tangent line is [tex]\[ y - 8 = \frac{6\sqrt{3}}{61}(x - \sqrt{3}) \][/tex]
- The normal line is [tex]\[ y - 8 = -\frac{61\sqrt{3}}{18}(x - \sqrt{3}) \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.